Research Context and Hotspots Analysis of WoS and CSSCI of Chemistry Education - Visual Knowledge Graph Analysis Based on CiteSpace - Aorigele; Natsagdorj Narantsogt (Lavai)
By collecting the literature related to the Chemistry Education from the Web of Science (WoS) and Chinese Social Sciences Citation Index (CSSCI) from 2000 to 2020, we used the CiteSpace bibliometric method to conduct inductive statistical analysis using the characteristics of age, author, country, research hotspot, and evolution trend. Our results revealed a significant growth trend of literature related to this field after 2009, but a stable core author group had not yet been formed. Our data also showed a lack of sufficient collaborative research among various groups. In this research field, the United States had the largest influence, followed by Germany and Australia. The trending literature was mainly focused on formal studies on the integration of Information Technology and Chemistry in courses, the interdisciplinary research on advanced chemistry courses, the reasons for the difficulties in students' understanding of chemical concepts and their solutions to approaching research, and models and modeling in addition to other subjects. Together, considering our results combined with the analysis of the literature citations, we further clarified the research progress and the current stage of Chemistry Education development.